A Structural Relationship of Entrepreneurial Orientation and Innovation through Supply Chain Management on Competitive Advantage of SMEs in North Sumatera, Indonesia: The Mediating Role of Financing Factor - Isfenti Sadalia; Harjum Muharam; Asep Mulyana; Jumadil Saputra; Rico Nur Ilham (International Journal of Supply Chain Management, 2020)
The complexity of economic activities, employment opportunities and significant contribution to the country generated through an instrument of entrepreneurial growth, namely Small and Medium Enterprises (SMEs). The primary objectives of this study are to examine the relationship of entrepreneurial orientation and innovation through supply chain management on competitive advantage and the role of financing factor as mediating variable in the relationship of entrepreneurial orientation and innovation on the competitive advantage of SMEs in North Sumatera, Indonesia. This study used a quantitative descriptive approach. A total of 300 respondents participated in this study. The data collected using random sampling technique and analyzed using the structural equation modelling (SEM) by assisting the statistical software, namely IBM AMOS-25. The results of the study show that entrepreneurial orientation and innovation have a significantly positive relationship on competitive advantages. Also, the financing factor mediates the relationship between entrepreneurial orientation and innovation on competitive advantages.